The Application of Next-Generation Sequencing for Mutation Detection in Autosomal-Dominant Hereditary Hearing Impairment. Issue 6 (July 2017) - Gürtler, Nicolas; Röthlisberger, Benno; Ludin, Katja; Schlegel, Christoph; Lalwani, Anil K.
Abstract : Objective: Identification of the causative mutation using next-generation sequencing in autosomal-dominant hereditary hearing impairment, as mutation analysis in hereditary hearing impairment by classic genetic methods, is hindered by the high heterogeneity of the disease. Patients: Two Swiss families with autosomal-dominant hereditary hearing impairment. Intervention: Amplified DNA libraries for next-generation sequencing were constructed from extracted genomic DNA, derived from peripheral blood, and enriched by a custom-made sequence capture library. Validated, pooled libraries were sequenced on an Illumina MiSeq instrument, 300 cycles and paired-end sequencing. Technical data analysis was performed with SeqMonk, variant analysis with GeneTalk or VariantStudio. The detection of mutations in genes related to hearing loss by next-generation sequencing was subsequently confirmed using specific polymerase-chain-reaction and Sanger sequencing. Main Outcome Measure: Mutation detection in hearing-loss-related genes. Results: The first family harbored the mutation c.5383+5delGTGA in the TECTA -gene. In the second family, a novel mutation c.2614-2625delCATGGCGCCGTG in the WFS1 -gene and a second mutation TCOF1- c.1028G>A were identified. Conclusion: Next-generation sequencing successfully identified the causative mutation in families with autosomal-dominant hereditary hearing impairment. The results helped to clarify the pathogenic role of a known mutation and led to the detection of a novel one. NGS represents a feasible approach with great potential future in the diagnostics of hereditary hearing impairment, even in smaller labs. Abstract : Supplemental Digital Content is available in the text